Marginal likelihood for Bayesian linear regression#

Author: Zeel B Patel, Nipun Batra

Bayesian linear regression is defined as below,

(18)#\[\begin{align} \mathbf{y} &= X\boldsymbol{\theta} + \epsilon\\ \epsilon &\sim \mathcal{N}(0, \sigma_n^2)\\ \theta &\sim \mathcal{N}(\mathbf{m}_0, S_0) \end{align}\]

For a Gaussian random variable \(\mathbf{z} \sim \mathcal{N}(\boldsymbol{\mu}, \Sigma)\), \(A\mathbf{z} + \mathbf{b}\) is also a Gaussian random variable.

(19)#\[\begin{align} \mathbf{y} = X\mathbf{\theta} + \boldsymbol{\epsilon} &\sim \mathcal{N}(\boldsymbol{\mu}', \Sigma')\\ \boldsymbol{\mu}' &= \mathbb{E}_{\theta, \epsilon}(X\mathbf{\theta}+\boldsymbol{\epsilon})\\ &= X\mathbb{E}(\mathbf{\theta}) + \mathbb{E}(\mathbf{\epsilon})\\ &= X\mathbf{m}_0\\ \\ \Sigma' &= V(X\mathbf{\theta}+\boldsymbol{\epsilon})\\ &= XV(\mathbf{\theta})X^T+V(\boldsymbol{\epsilon})\\ &= XS_0X^T + \sigma_n^2I \end{align}\]

Marginal likelihood is \(p(\mathbf{y})\) so,

(20)#\[\begin{align} p(\mathbf{y}) &= \frac{1}{(2\pi)^{\frac{N}{2}}|\Sigma'|^{\frac{1}{2}}}\exp\left[-\frac{1}{2}(\mathbf{y}-\boldsymbol{\mu}')^T\Sigma'^{-1}(\mathbf{y}-\boldsymbol{\mu}')\right]\\ &= \frac{1}{(2\pi)^{\frac{N}{2}}|XS_0X^T + \sigma_n^2I|^{\frac{1}{2}}}\exp\left[-\frac{1}{2}(\mathbf{y}-X\mathbf{m}_0)^T(XS_0X^T + \sigma_n^2I)^{-1}(\mathbf{y}-X\mathbf{m}_0)\right] \end{align}\]

Multiplication of two Gaussians (work in progress)#

We need Gaussian pdf over same variables to evaluate their multiplication. Let us convert \(y\) into \(\theta\).

(21)#\[\begin{align} \mathbf{y} &= X\theta + \boldsymbol{\epsilon}\\ \theta &= (X^TX)^{-1}X^T(\mathbf{y} - \boldsymbol{\epsilon})\\ \text{Deriving mean and covariance of }\theta\\ E(\theta) &= (X^TX)^{-1}X^T\mathbf{y}\\ V(\theta) &= \sigma_n^2\left[(X^TX)^{-1}X^T\right]\left[(X^TX)^{-1}X^T\right]^T\\ &= \sigma_n^2(X^TX)^{-1}X^TX(X^TX)^{-1}\\ &= \sigma_n^2(X^TX)^{-1} \end{align}\]

Now, we have both \(p(\mathbf{y}|\boldsymbol{\theta})\) and \(p(\boldsymbol{\theta})\) in terms of \(\boldsymbol{\theta}\). We can apply the rules from 6.5.2 of MML book. Writing our results in terminology of 6.5.2.

(22)#\[\begin{align} \mathcal{N}(x|a, A) &== \mathcal{N}(\theta|(X^TX)^{-1}X^T\mathbf{y}, \sigma_n^2(X^TX)^{-1})\\ \mathcal{N}(x|b, B) &== \mathcal{N}(\theta|\mathbf{m}_0, S_0) \end{align}\]

we know that,

\[\begin{split} c\mathcal{N}(\theta|\mathbf{c}, C) = \mathcal{N}(x|a, A)\mathcal{N}(x|b, B)\\ \mathcal{N}(\theta|\mathbf{c}, C) = \frac{\mathcal{N}(x|a, A)\mathcal{N}(x|b, B)}{c} \end{split}\]

In the Bayesian setting,

(23)#\[\begin{align} Prior &\sim \mathcal{N}(x|b, B) == \mathcal{N}(\theta|\mathbf{m}_0, S_0)\\ Likelihood &\sim \mathcal{N}(x|a, A) == \mathcal{N}(\theta|(X^TX)^{-1}X^T\mathbf{y}, \sigma_n^2(X^TX)^{-1})\\ Posterior &\sim \mathcal{N}(\theta|\mathbf{c}, C) == \mathcal{N}(\theta|\mathbf{m}_n, S_n)\\ \text{last but not the least}\\ Marginal\;likelihood &\sim c == \mathcal{N}(\mathbf{y}|\boldsymbol{\mu}, \Sigma) \end{align}\]

Let us evaluate the posterior,

(24)#\[\begin{align} Posterior &\sim \mathcal{N}(\theta|\mathbf{c}, C)\\ S_n = C &= (A^{-1} + B^{-1})^{-1}\\ &= \left(\frac{X^TX}{\sigma_n^2} + S_0^{-1}\right)^{-1}\\ \mathbf{m_n} = \mathbf{c} &= C(A^{-1}a + B^{-1}b)\\ &= S_n\left(\frac{X^TX}{\sigma_n^2}(X^TX)^{-1}X^T\mathbf{y} + S_0^{-1}\mathbf{m}_0\right)\\ &= S_n\left(\frac{X^T\mathbf{y}}{\sigma_n^2} + S_0^{-1}\mathbf{m}_0\right) \end{align}\]

Now, we evaluate the marginal likelihood,

(25)#\[\begin{align} c &= \mathcal{N}(\mathbf{y}|\boldsymbol{\mu}, \Sigma)\\ &= (2\pi)^{-\frac{D}{2}}|A+B|^{-\frac{1}{2}}\exp\left(-\frac{1}{2}(a-b)^T(A+B)^{-1}(a-b)\right)\\ &= (2\pi)^{-\frac{D}{2}}|\sigma_n^2(X^TX)^{-1}+S_0|^{-\frac{1}{2}}\exp\left(-\frac{1}{2}((X^TX)^{-1}X^T\mathbf{y}-\mathbf{m}_0)^T(\sigma_n^2(X^TX)^{-1}+S_0)^{-1}((X^TX)^{-1}X^T\mathbf{y}-\mathbf{m}_0)\right) \end{align}\]

Another well-known formulation of marginal likelihood is the following,

\[ p(\mathbf{y}) \sim \mathcal{N}(X\mathbf{m}_0, XS_0X^T + \sigma_n^2I) \]

Let us verify if both are the same, empirically,

import numpy as np
import scipy.stats
np.random.seed(0)

def ML1(X, y, m0, S0, sigma_n):
    N = len(y)
    return scipy.stats.multivariate_normal.pdf(y.ravel(), (X@m0).squeeze(), X@S0@X.T + np.eye(N)*sigma_n**2)

def ML2(X, y, m0, S0, sigma_n):
    D = len(m0)
    a = np.linalg.inv(X.T@X)@X.T@y
    b = m0
    A = np.linalg.inv(X.T@X)*sigma_n**2
    B = S0
    return scipy.stats.multivariate_normal.pdf(a.ravel(), b.ravel(), A+B)

def ML3(X, y, m0, S0, sigma_n):
    N = len(y)
    Sn = np.linalg.inv((X.T@X)/(sigma_n**2) + np.linalg.inv(S0))
    Mn = Sn@((X.T@y)/(sigma_n**2) + np.linalg.inv(S0)@m0)
    LML = -0.5*N*np.log(2*np.pi) - 0.5*N*np.log(sigma_n**2) - 0.5*np.log(np.linalg.det(S0)/np.linalg.det(Sn)) - 0.5*(y.T@y)/sigma_n**2 + 0.5*(Mn.T@np.linalg.inv(Sn)@Mn)
    return np.exp(LML)

X = np.random.rand(10,2)
m0 = np.random.rand(2,1)
s0 = np.random.rand(2,2)
S0 = s0@s0.T
sigma_n = 10
y = np.random.rand(10,1)

ML1(X, y, m0, S0, sigma_n), ML2(X, y, m0, S0, sigma_n),  ML3(X, y, m0, S0, sigma_n)
(9.577110083272389e-15, 0.0034284478634232078, array([[2.08309892e-14]]))

Products of Gaussian PDFs (Work under progress)#

Product of two Gaussians \(\mathbf{x} \sim \mathcal{N}(\boldsymbol{\mu}_0, \Sigma_0)\) and \(\mathbf{x} \sim \mathcal{N}(\boldsymbol{\mu}_1, \Sigma_1)\) is an unnormalized Gaussian.

(26)#\[\begin{align} f(\mathbf{x}) &= \frac{1}{(2\pi)^{\frac{N}{2}}|\Sigma_0|^{\frac{1}{2}}}\exp\left[-\frac{1}{2}(\mathbf{x}-\boldsymbol{\mu}_0)^T\Sigma_0^{-1}(\mathbf{x}-\boldsymbol{\mu}_0)\right]\\ g(\mathbf{x}) &= \frac{1}{(2\pi)^{\frac{N}{2}}|\Sigma_1|^{\frac{1}{2}}}\exp\left[-\frac{1}{2}(\mathbf{x}-\boldsymbol{\mu}_1)^T\Sigma_1^{-1}(\mathbf{x}-\boldsymbol{\mu}_1)\right]\\ \int h(x) = \frac{1}{c}\int f(\mathbf{x})g(\mathbf{x})d\mathbf{x} &= 1 \end{align}\]

We need to find figure out value of \(c\) to solve the integration.

(27)#\[\begin{align} h(x) &= \frac{1}{(2\pi)^{\frac{N}{2}}|\Sigma|^{\frac{1}{2}}}\exp\left[-\frac{1}{2}(\mathbf{x}-\boldsymbol{\mu})^T\Sigma^{-1}(\mathbf{x}-\boldsymbol{\mu})\right] = \frac{1}{(2\pi)^{\frac{N}{2}}|\Sigma|^{\frac{1}{2}}}\exp\left[-\frac{1}{2}\left(\mathbf{x}^T\Sigma^{-1}\mathbf{x} - 2\boldsymbol{\mu}^T\Sigma^{-1}\mathbf{x} + \boldsymbol{\mu}^T\Sigma^{-1}\boldsymbol{\mu}\right)\right]\\ f(x)g(x) &= \frac{1}{(2\pi)^{\frac{N}{2}}|\Sigma_0|^{\frac{1}{2}}(2\pi)^{\frac{N}{2}}|\Sigma_1|^{\frac{1}{2}}}\exp\left[ -\frac{1}{2}(\mathbf{x}-\boldsymbol{\mu}_0)^T\Sigma_0^{-1}(\mathbf{x}-\boldsymbol{\mu}_0) -\frac{1}{2}(\mathbf{x}-\boldsymbol{\mu}_1)^T\Sigma_1^{-1}(\mathbf{x}-\boldsymbol{\mu}_1)\right]\\ &= \frac{1}{(2\pi)^{\frac{N}{2}}|\Sigma_0|^{\frac{1}{2}}(2\pi)^{\frac{N}{2}}|\Sigma_1|^{\frac{1}{2}}}\exp\left[ -\frac{1}{2}\left(\mathbf{x}^T(\Sigma_0^{-1}+\Sigma_1^{-1})\mathbf{x}- 2\boldsymbol{\mu}^T(\Sigma_0^{-1}+\Sigma_1^{-1})\mathbf{x} + \boldsymbol{\mu}^T(\Sigma_0^{-1}+\Sigma_1^{-1})\boldsymbol{\mu}\right) \right]\\ \end{align}\]

We can compare the exponent terms directly. We get the following results by doing that

(28)#\[\begin{align} \Sigma^{-1} &= \Sigma_0^{-1} + \Sigma_1^{-1}\\ \Sigma &= \left(\Sigma_0^{-1} + \Sigma_1^{-1}\right)^{-1}\\ \\ \boldsymbol{\mu}^T\Sigma^{-1}\mathbf{x} &= \boldsymbol{\mu_0}^T\Sigma_0^{-1}\mathbf{x} + \boldsymbol{\mu_1}^T\Sigma_1^{-1}\mathbf{x}\\ \left(\boldsymbol{\mu}^T\Sigma^{-1}\right)\mathbf{x} &= \left(\boldsymbol{\mu_0}^T\Sigma_0^{-1} + \boldsymbol{\mu_1}^T\Sigma_1^{-1}\right)\mathbf{x}\\ \boldsymbol{\mu}^T\Sigma^{-1} &= \boldsymbol{\mu_0}^T\Sigma_0^{-1} + \boldsymbol{\mu_1}^T\Sigma_1^{-1}\\ \text{Applying transpose on both sides,}\\ \Sigma^{-1}\boldsymbol{\mu} &= \Sigma_0^{-1}\boldsymbol{\mu}_0 + \Sigma_1^{-1}\boldsymbol{\mu}_1\\ \boldsymbol{\mu} &= \Sigma\left(\Sigma_0^{-1}\boldsymbol{\mu}_0 + \Sigma_1^{-1}\boldsymbol{\mu}_1\right) \end{align}\]

Now, solving for the normalizing constant \(c\),

(29)#\[\begin{align} \frac{c}{(2\pi)^{\frac{N}{2}}|\Sigma|^{\frac{1}{2}}} &= \frac{1}{(2\pi)^{\frac{N}{2}}|\Sigma_0|^{\frac{1}{2}}(2\pi)^{\frac{N}{2}}|\Sigma_1|^{\frac{1}{2}}}\\ c &= \frac{|\Sigma|^{\frac{1}{2}}}{(2\pi)^{\frac{N}{2}}|\Sigma_0|^{\frac{1}{2}}|\Sigma_1|^{\frac{1}{2}}} \end{align}\]

If we have two Gaussians \(\mathcal{N}(\mathbf{a}, A)\) and \(\mathcal{N}(\mathbf{b}, B)\) for same random variable \(\mathbf{x}\), Marginal likelihood can be given as,

\[ c = (2\pi)^{-N/2}|A+B|^{-1/2}\exp -\frac{1}{2}\left[(\mathbf{a} - \mathbf{b})^T(A+B)^{-1}(\mathbf{a} - \mathbf{b})\right] \]

Here, we have two Gaussians \(\mathcal{N}(0, \sigma^2I)\) and \(\mathcal{N}((X^TX)^{-1}X^T\mathbf{y}, \frac{(X^TX)^{-1}}{\sigma_n^2} )\) for same random variable \(\boldsymbol{\theta}\), Marginal likelihood can be given as,

\[\]
import numpy as np
import matplotlib.pyplot as plt
import scipy.stats
np.random.seed(0)
N = 10
D = 5
sigma_n = 0.1 # noise
sigma = 1 # variance in parameters
m0 = np.random.rand(D)
S0 = np.eye(D)*sigma**2

x = np.random.rand(N,D)
theta = np.random.rand(D,1)
y = x@theta + np.random.multivariate_normal(np.zeros(N), np.eye(N)*sigma_n**2, size=1).T
plt.scatter(x[:,0], x[:,1], c=y)
x.shape, theta.shape, y.shape
((10, 5), (5, 1), (10, 1))
../../_images/2021-03-31-derivation-of-marginal-likelihood_13_1.png
a = np.linalg.inv(x.T@x)@x.T@y
b = m0.reshape(-1,1)
A = np.linalg.inv(x.T@x)/(sigma_n**2)
B = S0
A_inv = np.linalg.inv(A)
B_inv = np.linalg.inv(B)

c_cov = np.linalg.inv(A_inv + B_inv)
c_mean = c_cov@(A_inv@a + B_inv@b)
a.shape, A.shape, b.shape, B.shape, c_mean.shape, c_cov.shape
((5, 1), (5, 5), (5, 1), (5, 5), (5, 1), (5, 5))
c_denom = 1/(((2*np.pi)**(D/2))*(np.linalg.det(c_cov)**0.5))
b_denom = 1/(((2*np.pi)**(D/2))*(np.linalg.det(B)**0.5))
a_denom = 1/(((2*np.pi)**(D/2))*(np.linalg.det(A)**0.5))
a_denom, b_denom, c_denom, 1/c_denom
(1.5040129154541655e-07,
 0.010105326013811642,
 0.0110028525380197,
 90.88552232655665)
normalizer_c = (1/(((2*np.pi)**(D/2))*(np.linalg.det(A+B)**0.5)))*np.exp(-0.5*((a-b).T@np.linalg.inv(A+B)@(a-b)))
norm_c_a_given_b = scipy.stats.multivariate_normal.pdf(a.squeeze(), b.squeeze(), A+B)
norm_c_b_given_a = scipy.stats.multivariate_normal.pdf(b.squeeze(), a.squeeze(), A+B)
normalizer_c, norm_c_a_given_b, norm_c_b_given_a, 1/normalizer_c
(array([[1.35765194e-07]]),
 1.357651942204283e-07,
 1.357651942204283e-07,
 array([[7365658.08152844]]))
a_pdf = scipy.stats.multivariate_normal.pdf(theta.squeeze(), a.squeeze(), A)
b_pdf = scipy.stats.multivariate_normal.pdf(theta.squeeze(), b.squeeze(), B)
c_pdf = scipy.stats.multivariate_normal.pdf(theta.squeeze(), c_mean.squeeze(), c_cov)

a_pdf, b_pdf, c_pdf, np.allclose(a_pdf*b_pdf, normalizer_c*c_pdf)
(1.5039199356435742e-07, 0.008635160418150373, 0.00956547808509135, True)
K = x@S0@x.T + np.eye(N)*sigma_n**2
marginal_Likelihood_closed_form = scipy.stats.multivariate_normal.pdf(y.squeeze(), (x@m0).squeeze(), K)
marginal_Likelihood_closed_form, 1/normalizer_c
(1.8288404157840938, array([[7365658.08152844]]))
from sklearn.model_selection import KFold
from sklearn.linear_model import LinearRegression

splitter = KFold(n_splits=100)
for train_ind, test_ind in splitter(x):
    train_x, train_y = x[train_ind], y[train_ind]
    test_x, test_y = x[test_ind], y[test_ind]
    model = LinearRegression()
    model.fit(train_x, train_y)
    
---------------------------------------------------------------------------
TypeError                                 Traceback (most recent call last)
<ipython-input-75-224c1ff02397> in <module>
      3 
      4 splitter = KFold(n_splits=100)
----> 5 for train_ind, test_ind in splitter(x):
      6     train_x, train_y = x[train_ind], y[train_ind]
      7     test_x, test_y = x[test_ind], y[test_ind]

TypeError: 'KFold' object is not callable

What is the relationship between marginal_Likelihood_closed_form and any calculations done in multiplications of two gaussians?#